Proses Berpikir Aljabar Siswa Field dependent dan Field independent dalam Menyelesaikan Masalah Matematika Berdasarkan Teori APOS - Oktawioni, Rossa Tri; Ekawati, Rooselyna (MATHEdunesa, 2025)
Algebraic thinking is a mental activity that involves analyzing relationships between quantities, observing structure, understanding changes, generalizing, modeling, justifying, proving, and predicting based on expressions and symbols that appear in solving algebraic problems. This research describes the algebraic thinking process of field-dependent and field-independent students in solving mathematical problems based on APOS (Action-Process-Object-Scheme) theory. This type of research is descriptive with a qualitative approach. The data in this study consisted of the results of the Group Embedded Figures Test (GEFT), Mathematics Ability Test (TKM), Algebraic Thinking Ability Test (TKBA), and interviews. The research subjects were eighth-grade students consisting of one field-dependent and field-independent student, each with high mathematical abilities and male gender as the control variable. Based on the research that has been carried out, the following results were obtained: (1) Students with a field-dependent cognitive style carry out the Action, Process, Object stages, and fulfill one of the Schemes, and have a tendency towards transformation activities in solving mathematical problems on number pattern material. (2) Students with a field-independent cognitive style carry out the Action, Process, and Object stages, fulfill all Schemes well, and tend towards generalization activities in solving mathematical problems on number pattern material.